(untitled) (Namibian Journal for Research, Science and Technology, 2020)
Ongoing studies in the Namaqua Sector, situated in the Namaqua-Natal Metamorphic Province (NNMP), have been vital in understanding the geological activities that occurred during the Rodinia supercontinent assembly. These geological activities are usually key to discovering new mineral raw materials. The Tschaukaib Granitic Suite, which is believed to be part of the Gordonia Thrust Stack (GTS) of the Kakamas Domain, crops out within Tschaukaib Mountains and was characterized in this study on the basis of surface mapping, petrographic and major element geochemistry. Three types of granites were identified, namely: granodiorite, quartz monzonite and granite with SiO2 content ranging from 64.9 wt % to 69.8 wt %. Whole rock geochemistry further shows that they are calc-alkaline, alkalicalcic, ferroan, peraluminous (Al2O3 > K2O + Na2O + CaO) and have >1 % Cross, Iddings, Pirsson and Washington (CIPW) corundum. The geochemical characteristics indicates that the granitoids were emplaced during the continental collision and are formed from partial melting of recycled crustal material which took place during the Rodinia supercontinent. The geochemistry shows a conspicuous fractional crystallization signature. Geological mapping and structural analysis of the Tschaukaib Granitic Suite area shows a NW-SE and E-W trending regional foliation in the Tschaukaib Augen Gneiss (quartz monzonite) which corresponds to the main D2 Namaqua metamorphic event. Several shear zones were mapped and are consistent to the Pofadder Shear Zone which runs in the NW-SE and E-W directions, parallel to the study area. Petrographic analysis of the granitoids has identified mineral assemblages which shows that the granitoids have undergone high strain and alterations, however, it is not clear which Namaqua deformation episode brought about these features.